Pemanfaatan Tik-Tok Sebagai Media Dakwah: (Studi Kasus Ustad Syam, di akun @syam_elmarusy) - Ayu Febriana (KOMUNIDA : Media Komunikasi dan Dakwah, 2021)
study aims to analyze the potential of Tik-Tok social media as a new medium in conveying da'wah messages and then analyze its weaknesses and strengths. The method used in this study is a descriptive qualitative method with data sources in the form of documents, video postings from social media accounts with analytical methods relating to theories related to da'wah media, da'wah messages and also new media. The results show that Tik-Tok can be optimized for the purpose of conveying da'wah messages as exemplified by Ustaz Syam in the @syam_elmarusy account using Tik-Tok's advantages, namely an attractive visual appearance. With this display, Ustaz Syam conveyed a message of da'wah that was still based on the Qur'an and Hadith with da'wah konten ranging from Islamic teachings in it, related to aqidah, sharia and morals/muamalah with the aim of making it easily accepted by generations of Tik-Tok users as da'wah partners.